The Case Against 2 Per Cent Inflation From Negative Interest Rates to a 21st Century Gold Standard - Brown, Brendan (Springer International Publishing, 2018)
This book analyses the controversial and critical issue of 2% inflation targeting, currently practised by central banks in the US, Japan and Europe. Where did the 2% target inflation originate, and for what reason? Do these reasons stand up to scrutiny? This book explores these key questions, contributing to the growing debate that the global 2% inflation standard prescribed by the central banks in the advanced economies globally is actually contributing to the economic malaise of these nations. It presents novel theoretical perspectives, intertwined with historical and market understanding, and features analysis that draws on monetary theory (including Austrian school), behavioural finance, and finance theory. Alongside rigorous analysis of the past and present, the book also features forward looking chapters, exploring how the 2% global inflation standard could collapse and what would ideally follow its demise, including a new look at the role of gold.